2016
DOI: 10.1111/rda.12850
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear and developmental competence of cumulus–oocyte complexes is enhanced by three‐dimensional coculture with conspecific denuded oocytes during in vitro maturation in the domestic cat model

Abstract: Contents The objective of the study was to assess the efficacy of coculture with conspecific cumulus‐denuded oocytes (CDOs) during in vitro maturation in a three‐dimensional system of barium alginate microcapsules on the in vitro embryo development of domestic cat cumulus–oocyte complexes (COCs). In Experiment I, COCs were cocultured with conspecific CDOs or cultured separately in a 3D system for 24 hr of in vitro maturation, before assessing the meiotic progression. In Experiment II, the in vitro fertilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…These encouraging results suggest a positive role of alginate microcapsules in providing better environmental conditions for a prolonged culture of oocytes in vitro. As already reported in other species, biocompatible structures can enhance the maintenance of the physiological architecture of female gametes and their molecular, metabolic and developmental competence (Desai et al, 2010;Morselli, Luvoni, & Comizzoli, 2017;Pangas et al, 2003). In comparison with the traditional 2D culture (microdrops of medium in Petri dishes or multiwell), the 3D systems sustain the survival and the growth of cultured cells, promoting the cytoplasmic and nuclear maturation of oocytes and the subsequent embryo development.…”
Section: Discussionmentioning
confidence: 88%
“…These encouraging results suggest a positive role of alginate microcapsules in providing better environmental conditions for a prolonged culture of oocytes in vitro. As already reported in other species, biocompatible structures can enhance the maintenance of the physiological architecture of female gametes and their molecular, metabolic and developmental competence (Desai et al, 2010;Morselli, Luvoni, & Comizzoli, 2017;Pangas et al, 2003). In comparison with the traditional 2D culture (microdrops of medium in Petri dishes or multiwell), the 3D systems sustain the survival and the growth of cultured cells, promoting the cytoplasmic and nuclear maturation of oocytes and the subsequent embryo development.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies showed that the 3D barium alginate microcapsules were used to culture feline oocytes (Morselli, Canziani, Canziani, Vigo, & Luvoni, 2017) and domestic cat oocytes (Morselli, Luvoni, Luvoni, & Comizzoli, 2017) to improve the cumulus-denuded oocyte full competence. Meanwhile, the 3D culture systems were also used in buffalo preantral follicles with collagen gel (Sharma, Dubey, & Meur, 2009) and the denuded oocytes with ovarian tissue (Feng, Shi, Yang, & Wang, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our work on 3D barium alginate microcapsules for the in vitro culture of feline oocytes gave encouraging results in terms of oocyte full nuclear maturation (Morselli, Canziani, Vigo, & Luvoni, 2017) and embryo development (Morselli, Luvoni, & Comizzoli, 2017), together with a significant positive effect of co-culturing fresh COCs with companion denuded ad hoc oocytes.…”
Section: Physical Factorsmentioning
confidence: 88%
“…With the aim of recreating a physical contact between gametes or embryos and somatic cells, different co‐culture systems (granulosa and oviductal cells: Chigioni, Perego, & Luvoni, ; Roth, Donoghue, Byers, Wildt, & Munson, ; Swanson, Roth, & Godke, ) were tested. In addition, co‐culture of cat COCs with cumulus denuded oocytes as companion cells gave promising results in terms of meiosis resumption and embryo development rates (Godard, Pukazhenthi, Wildt, & Comizzoli, ; Morselli, Luvoni, & Comizzoli, ). Same beneficial effects of the co‐culture have been obtained with embryos cultured in groups rather than alone (Spindler & Wildt, ).…”
Section: Introductionmentioning
confidence: 99%